Complex formation of anti‐VEGF‐C with VEGF‐C released during blood coagulation resulted in an artifact in its serum pharmacokinetics - Daniela Bumbaca Yadav; Arthur E. Reyes II; Priyanka Gupta; Jean‐Michel Vernes; Y. Gloria Meng; Michelle G. Schweiger; Shannon L. Stainton; Germaine Fuh; Paul J. Fielder; Amrita V. Kamath; Ben‐Quan Shen (Wiley, 2020)
Abstract A phage‐derived human monoclonal antibody against VEGF‐C was developed as a potential anti‐tumor therapeutic and exhibited fast clearance in preclinical species, with notably faster clearance in serum than in plasma. The purpose of this work was to understand the factors contributing to its fast clearance. In vitro incubations in animal and human blood, plasma, and serum were conducted with radiolabeled anti‐VEGF‐C to determine potential protein and cell‐based interactions with the antibody as well as any matrix‐dependent recovery dependent upon the matrix. A tissue distribution study was conducted in mice with and without heparin infusion in order to identify a tissue sink and determine whether heparin could affect antibody recovery from serum and/or plasma. Incubation of radiolabeled anti‐VEGF‐C in human and animal blood, plasma, or serum revealed that the antibody formed a complex with an endogenous protein, likely VEGF‐C. This complex was trapped within the blood clot during serum preparation from blood, but not within the blood cell pellet during plasma preparation. Low level heparin infusion in mice slowed down clot formation during serum preparation and allowed for better recovery of the radiolabeled antibody in serum. No tissue sink was found in mice. Thus, during this characterization, we determined that the blood sampling matrix greatly impacted the amount of antibody recovered in the samples, therefore, altering its derived pharmacokinetic parameters. Target biology should be considered when selecting appropriate sampling matrices for PK analysis.